An Urgent Need to Incorporate Evidence-Based Nutrition and Lifestyle Medicine Into Medical Training. Issue 1 (January 2019) - Reddy, Koushik R.; Freeman, Andrew M.; Esselstyn, Caldwell B.
It is well established that evidence based clinical nutrition and lifestyle practices play a pivotal role in the prevention, treatment and potential reversal of various common chronic diseases. However, this area of science is under appreciated at all levels of medical education and training. Most medical schools and residency programs do not offer any organized training in nutrition and lifestyle medicine. Given recent data on the rising cost and loss of quality of life secondary to preventable causes, there is an absolute need for a drastic reform of the US medical education system.